Disrupt and Deny : spies, special forces, and the secret pursuit of British foreign policy - Cormac, Rory (UK: New York: Oxford University Press, 2018)
British leaders use spies and Special Forces to interfere in the affairs of others discreetly and deniably. Since 1945, MI6 has spread misinformation designed to divide and discredit targets from the Middle East to Eastern Europe and Northern Ireland. It has instigated whispering campaigns and planted false evidence on officials working behind the Iron Curtain, tried to ferment revolution in Albania, blown up ships to prevent the passage of refugees to Israel, and secretly funneled aid to insurgents in Afghanistan and dissidents in Poland. MI6 has launched cultural and economic warfare against Iceland and Czechoslovakia. It has tried to instigate coups in Congo, Egypt, Syria, Saudi Arabia, Iran, and elsewhere. Through bribery and blackmail, Britain has rigged elections as colonies moved to independence. Britain has fought secret wars in Yemen, Indonesia, and Oman and discreetly used Special Forces to eliminate enemies from colonial Malaya to Libya during the Arab Spring. Rory Cormac tells the remarkable true story of Britain's secret scheming against its enemies, as well as its friends; and, above all, of Britain's attempt to use smoke and mirrors to mask decline.
Introduction: Covert action -- Part one: Cold war (1. False starts: fromcounter-attack to liberation ; 2. Operation Valuable: defending Greece, detaching Albania ; 3. Pinpricks: the early Cold War ; 4. A long game: exploring rifts behind the Iron Curtain) -- Part two: The end of Empire (5. Operation Boot: regime change in Iran ; 6. Expansion: covert action before Suez ; 7. Interdependence: covert action after Suez ; 8. Decolonization and drift: the battle for influence after Empire ; 9. Militarization: secret wars in Yemen and Indonesia) -- Part three: Age of illusions (10. Operations Storm and Beyond: from Latin America to Oman ; 11. Troubles: covert action in northern Ireland ; 12. Containment: the Second Coldv war ; 13. Transition: the new agenda ; 14. Counter-terrorism: disrupting threats, managing risks) -- Conclusion: The British way.
Includes bibliographical references (pages 359-380) and index.
Keywords: Intelligence service -- Great Britain -- History; Spies -- Great Britain -- History; Disinformation -- Great Britain -- History; Secret service -- Great Britain -- History; Disinformation; Intelligence service; Secret service; Spies; Great Britain; History